Przemówienie wicepremiera rządu jugosłowiańskiego Edvarda Kardelja w związku z przyjęciem Ustawy o Radach Ludowych, wygłoszone w Skupsztynie 28 maja 1949 roku (Tabularium Historiae, 2017)
Edvard Kardelj was one of the most important politician-theoretic of the Yugoslav Communist Party. Next to Josip Broz-Tito and Milovan Djilas, was responsible for a new internal policy of Yugoslavia after split with Soviet Union in 1948 r. People’s Councils, even though this institution wasn’t new in Marxist’s theory, got special meaning in Yugoslav reality. Kardelj claimed, that Yugoslav way in “making socialism” is more “democratic”, than in other countries in Eastern block. This “democracy” had to be functioning, when the strongest terror from secret police appeared. In addition, the content of speech has strictly ideological and political sense, which stands in opposition to the authentic policy of the leaders of the Yugoslav state.